Quantifying the jump height in vertical jumping with two different evaluation concepts - Schwieger, K.; Baca, A. (International Journal of Performance Analysis in Sport, 2002)
When evaluating jumping performance two different concepts are most frequently applied for quantifying jump height. In many investigations jump height is defined as the flight height (hflight), i.e. lifting height of the body´s center of mass (CM) from the liftoff position (htakeoff) to the vertex of the flight trajectory. In other studies the jump height is defined as the difference between the height of the CM at the apex of the jump and the height of the CM in upright standing (htotal). The purpose of this study was to compare these concepts. In addition, the study was undertaken to gain deeper insight in the relationship between htakeoff and hflight. 230 jumps (10 per subject) were selected for the comparisons. Force plate data were used to compute both kinds of jump height. The mean difference between htotal of the best trial and that with highest hflight (10 trials per subject) was 0.33 ±0.56 % (1.53 ± 2.37 mm) indicating that it is more or less alike which parameter to use in order to identify the best trial of a jump series. Spearman´s coefficient between htakeoff and hflight ranged from -0.503 to 0.842 (mean: 0.117) and did not show a general tendency (one-sample t-test: p>0.2). The reason might be individual differences in motor control stategies.